A mosaic approach can advance the understanding and conservation of native biodiversity in natural and fragmented riverscapes - Hitchman, Sean M. (Kansas State University, 2018)
Understanding the complex relationship between organismal distribution and spatial heterogeneity is central to many ecological questions. This challenge of identifying the biodiversity consequences of spatial patterns is especially critical for resource conservation at the larger riverscape scale because climate- and human-related impacts often act through intricate and spatially-connected organismal-habitat relationships. Specifically, resource managers cannot manage the adverse effects of common disturbances on aquatic ecosystems (e.g. water-withdrawal, dams, urbanization) if the influence of spatial heterogeneity is not recognized and understood. Towards this larger goal, I examined the role of spatial heterogeneity on stream fish biodiversity in the Upper Neosho River, KS in three ways. First, I used a mosaic approach (in which connected, interacting collections of juxtaposed habitat patches were examined) to build the scientific foundation for a general model that aids in the understanding and environmental management of disturbance-related, ecologically-based conservation problems. Second, I examined landscape metrics to quantify the impact of low-head dams on stream habitat and fish diversity. Third, I evaluated multiple quantitative approaches to develop a fuller understanding of how the arrangement of habitats across the riverscape influenced stream fish biodiversity. Related to these questions, the dissertation research provided four key take-home messages that advanced science-based conservation related to stream fish habitat and biodiversity. First, mapping larger-scale patterns of heterogeneity showed that quantitatively-different, physically-distinct pool, riffle, run, and glide habitats were arranged in unique combinations created diverse habitat mosaics across sites. Second, riffles, which comprised < 5% of all habitat patches, acted as keystone habitats that disproportionately increased fish biodiversity (i.e., species richness was significantly higher in mosaics with higher numbers of riffles). Third, mosaic approach metrics provided new insights into the influence of low-head dams on stream fish biodiversity that were not detected with traditional approaches to habitat sampling and statistical analysis. For example, low-head dams dampened the natural habitat diversity that is needed for the maintenance of resilient communities. Furthermore, using path analysis, I found that species richness was higher immediately below low-head dams as mediated through an increase in the proportion of riffle habitat, but this higher species richness was offset by a greater decrease in species richness in the impoundment habitat above low-head dams. Thus, the choice of scale influenced the interpretation of how dams affected habitat heterogeneity and resultant organismal patterns. Finally, landscape approaches to examining compositional and configurational heterogeneity provided new insights about stream fish habitat-biodiversity relationships. For example, riffle patch density had a positive effect on species richness, species richness was higher within shallow, slow flowing riffles, and adjacent neighbor habitats affected riffle species richness as mediated through alterations to within-habitat characteristics. In summary, quantifying the complex patterns of spatial heterogeneity in a range of ways can aid in the understanding of habitat-biodiversity patterns and help conserve stream fishes at a variety of scales.
Keywords: Fish; Habitat; Biodiversity; KeystoneMosaics